Menentukan Masa Depan: Pentingnya Pengelolaan Keuangan Purnabhakti Atlit - Susetyo, Aris; Yogi Ardiansah; Yuyun Setiawati (JCSE: Journal of Community Service and Empowerment, 2023)
Financial planning is a very important aspect to ensure your future after ending your career. An athlete's prime does not last long, the golden age is very short while the life expectancy is long. Therefore, good financial planning is needed to meet your needs in old age. The purpose of service activities provides an illustration of how important proper financial management is for athletes after they retire. By focusing on financial planning, discipline, smart investment and financial protection, retired athletes can ensure financial stability in overcoming financial challenges that arise in the future. Through a good understanding of financial management, athletes are expected to be able to maintain their quality of life with confidence. Good financial management is the key to ensuring that after retirement, athletes can pursue their dreams after retiring from the world of sport.